Plasmon-induced transparency in graphene-based terahertz metamaterials. (15th January 2018) - Devi, Koijam Monika; Islam, Maidul; Chowdhury, Dibakar Roy; Sarma, Amarendra K.; Kumar, Gagan
Abstract: Plasmon-induced transparency (PIT) effect in a terahertz graphene metamaterial is numerically and theoretically analyzed. The proposed metamaterial comprises of a pair of graphene split ring resonators placed alternately on both sides of a graphene strip of nanometer scale. The PIT effect in the graphene metamaterial is studied for different vertical and horizontal configurations. We have shown that the PIT effect can be tuned by varying the Fermi energy of the graphene layer. A theoretical model using the three-level plasmonic system is established in order to validate the numerical results. Our studies could be significant in designing graphene-based frequency agile ultra-thin devices for terahertz applications.